Malignant transformation of endometrial hyperplastic processes: immunohistochemical features - M. S. Sobivchak; A. E. Protasova; G. A. Raskin; M. S. Mukhina; A. S. Kaurtseva (ABV-press, 2022)
Background. Endometrial hyperplasia is one of the most common pathologies of the female reproductive system. There is a high risk of transformation of an atypical form of endometrial hyperplasia into endometrial cancer, which takes a leading position in oncogynecological morbidity. Immunohistochemical markers can become predictors of endometrial malignancy, their role is currently being actively studied.Aim. Search for molecular predictors of malignant transformation of endometrial hyperplasia.Materials and methods. Histological and immunohistochemical studies were performed in 107 patients with diagnoses of endometrial hyperplasia without atypia (EH), endometrial atypical hyperplasia (EIN), endometrioid adenocarcinoma (EC). The tumor receptor status, MSI, expression of ARID1A, PTEN, β-catenin, PAX2, proliferation index (Ki-67) were determined by the immunohistochemical method according to the standard protocol.Results. Loss of PAX2 expression was most common in precancerous and malignant endometrial cells. Loss of PAX2 expression was found in 89 % of cases in the EIN samples, in 86 % of cases in the EC samples and only in 2 cases of EH. Loss of PTEN expression was less common: with an equal proportion in 67 % of the samples of EIN and EC, while practically not occurring in women with benign GE. MSI was detected in 36 % of endometrial cancer samples. There was a deficiency in the DNA repair system in 1 case of EIN. Loss of ARID1A expression was detected in endometrial cancer with a frequency of 33 %. This gene functioned normally in all cases of EIN and EH. The expression of β-catenin was more pronounced in EC than in cases of EH. The Ki-67 proliferation index was statistically higher in the EC group than in EH and EIN.Conclusion. Evaluation of morphological data and expression of the panel of markers PAX2, PTEN, ARID1A, β-catenin, Ki-67 index, PMS2 and MLH1 will improve diagnostic search in case of suspected malignancy of endometrial hyperplasia.